PERUBAHAN PARADIGMA PEMBANGUNAN SEKTOR KEHUTANAN DI INDONESIA: TANTANGAN DAN PELUANG DALAM KONTEKS KEBERLANJUTAN - Santoso, Wiji Johar (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
The forestry development paradigm in Indonesia has undergone various changes, especially in an effort to achieve a balance between economic growth, environmental conservation, and community welfare. This article will discuss the paradigm shift in the development of the forestry sector starting from the exploitation of forests for purely economic interests to a sustainability approach that integrates ecological, social, and economic aspects. The study also explores the challenges and opportunities that arise with the implementation of sustainable forestry policies in Indonesia, and the important role of stakeholders in realizing more equitable and responsible forest management.